2020
DOI: 10.18517/ijaseit.10.1.11012
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Electrocogulation and Aeration Processes by Addition NaCl for Leachate Treatment

Abstract: Leachate is water which is formed in a pile of garbage that dissolves a lot of existing compounds so that it has a very high pollutant content, especially organics substances. Leachate has the potential to cause water pollution, both surface water, ground water and underground water, so it needs to be managed properly. Leachate processing uses a combination of electrocoagulation and aeration methods. The objective of this study is to determine leachate characteristics before and after the processes, the optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Therefore, in this research, the novel method of zeolite (clinoptilolite) augmentation on the electrocoagulation process was investigated as a co‐treatment for the elimination of high‐strength ammonia and color from a saline landfill leachate which acts as a natural electrolyte. Furthermore, there is no additional electrolyte needed in this study as opposed to many other studies by Mohajeri et al (2018), Kumar and Sharma (2019), and Rusdianasari et al (2020). In addition, in the current work, the leachate concentrations were in a stabilized form, more concentrated and not easily amendable by biological process.…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, in this research, the novel method of zeolite (clinoptilolite) augmentation on the electrocoagulation process was investigated as a co‐treatment for the elimination of high‐strength ammonia and color from a saline landfill leachate which acts as a natural electrolyte. Furthermore, there is no additional electrolyte needed in this study as opposed to many other studies by Mohajeri et al (2018), Kumar and Sharma (2019), and Rusdianasari et al (2020). In addition, in the current work, the leachate concentrations were in a stabilized form, more concentrated and not easily amendable by biological process.…”
Section: Introductionmentioning
confidence: 84%
“…Wahidah [9] stated that as pH increases to alkaline, the ions will coagulate in a weaker state which reduce the removal performances. In general, the pH of the sample will be varied when the EC carried out depends on the electrode materials and initial pH [24], during the process as result of the H2O oxidation reactions generated at the cathode, and successive OHions are formed in the electrolytic medium [25]. The result of the study found the optimal removal of colour and ammonia nitrogen were 68.65% and 48.30% respectively and found the highest removal percentage both at pH 5.…”
Section: Effect Of Phmentioning
confidence: 97%
“…The same research shows Colour Ammonia that the maximum removal efficiency of NH₃-N occurs at initial pH of 7.5, with the percentage of NH₃-N removal at 25.3%. Increasing in pH in the EC process was due to the production of hydrogen at the cathode electrode and the discharge of hydroxide ions from ferum hydroxide [12]. For colour removal, [20] carried out an AEC experiment for distillery spent wash by using aluminium and ferum electrodes, the results of the studies showing the maximum colour removal happened at 25 V of current density and pH 8 with the percentage of colour removal was 99.78%.…”
Section: Expected Optimum Range For Phmentioning
confidence: 99%